KONTRIBUSI AGROFORESTRI TERHADAP PENDAPATAN RUMAH TANGGA PETANI - Dewi, Mega Nurkumala; Nurlaila, Ai; Karyaningsih, Ika (Journal of Forestry And Environment, 2024)
Agroforestry is a land use system that combines agricultural crops with forestry plants which are generally carried out in order to obtain maximum income. This study aims to determine the level of income of agroforestry farmers, how much farmer income contributes and to determine the factors that affect agroforestry farmers’ income. This study used an interview method with 41 agroforestry farmers and was conducted in December-April 2020 in Karangsari Village, Kuningan Regency. Karangsari village has 38 types of plants that are used to generate economic value for farmers’ income, the income that farmers get from agroforestry is Rp. 2,071,796,500 and farmers’ income from non-agroforestry products amounting to Rp. 2,481,600,000 so that it can be seen that the contribution of management with an agroforestry system to farmers’ income is 46%, while the contribution of non-agroforestry is 54%. Factors that can affect farmers’ income are land area factors. This is because the larger the land area, the more various types of plants and the more yields you get.